Agricultural policies, land-use and waterbird conservation: the case study of a major Mediterranean wetland, the Camargue - Raphaël Mathevet; Christophe Tourenq; François Mesléard (Cybergeo, 2002)
This paper explores the role of agricultural policies on the ricefield area dynamic in the Camargue, a Mediterranean wetland of international importance for waterbird conservation. Rice is the most common crop in the Rhone delta and earlier studies have highlighted the strong complementarity of rice fields with natural habitats for waterbirds. Modifications of agriculture-environment interactions are tackled through two main bird groups, of conservation interest, using ricefields for feeding purposes: colonial herons and flamingos. The regional history, concerning land-use and rice-farming changes, reveals the ways in which the local landscape has changed as the national and supranational agricultural policies have developed since WWII. The importance of the increase of ricefield area for colonial herons as well as the role of ricefield landscape modifications on the crop damages by flamingos are examined. They illustrate how wildlife and farming interact in a complex manner, which needs to be understood in order to develop agricultural practices adapted to the environment and to promote integrated environmental policies. The authors suggest that a better understanding of the role which agricultural policies play on a region’s development history and geography is fundamental to any conservation policy analysis.